PERBANDINGAN ANGKA KEBERHASILAN ANESTESI SPINAL DENGAN PENDEKATAN PARAMEDIAN DAN PENDEKATAN MEDIAN PADA PASIEN GERIATRI - ISNAENI, NURUL ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Background: Subarachnoid block has been generally done from median approach. This kind of approach on geriatric patients frequently is more difficult due to various problems from arthritis, inflammatory joints, spine structures degenerative changes, both inter or supraspinous calcifications. Another approach choice is paramedian technique, which could be useful on degenerative changes on interspinous structures, either barely even affected by osteoarthritis changes nor flexion head position. Methods: The research was a randomized controlled trial study with 134 geriatric patients (≥65 years), ASA 1-2, BMI 20-30 kg/m2 who underwent spinal anesthesia for surgeries. After randomization, the subjects were then divided into two separate groups; Group PM was given spinal anesthesia with paramedian approach while group M with median approach. The patients were positioned in sitting position with punctured sites at VL 3-4 level. The primary outcome assessment was the appearance of Cerebrospinal fluid (CSF) through the needle of spinal anesthesia on first attempt. The secondary outcome were the number of spinal needle position, site point of injection, bloody tap and appropriate depth of the needle. After local anesthesia had reached the subarachnoid space, the procedure was completed and the monitoring was proceed until the operation finished. Results: The success rate after the first attempt was 95.5% for group PM and 80.5% for group M (p=0.007). The appearance of Cerebrospinal fluid (CSF) of group PM was found 100% and 95.5% for group M. Bloody tap after needle puncture was observed in 7 patients in group PM vs 2 in group M (p=0.01), but there were no significant clinical complications could observed. Conclusion: The paramedian approach is associated with an increased success rate of spinal anesthesia on a first attempt, compared with the median approach for geriatric patients.